HUBUNGAN PENGGUNAAN FASILITAS BELAJAR SISWA DENGAN HASIL BELAJAR SENI BUDAYA BIDANG SENI RUPA DI SMPN 1 BATANG ANAI - SANTI, Wisdiarman, Yusron Wikarya (Serupa The Journal of Art Education, 2013)
The purpose of these study was to determine the relationship of students’ facility with the learning outcomes of arts and culture in the fild of visual art at SMPN 1 Batang Anai. The research hypothesis is there is a significant relationship between the use of students’ facility with the learning outcomes of cultural arts in the field of visual arts at SMPN 1 Batang Anai. The study population was all students from 10 class. The study sample class VII. The technique of data collection is use a questionnaire to respondents, while the data of students learning out comes obtained from Arts teacher. Type of research is purposive sampling. The findings of the study indicated that the calculation results revealed that the correlation coefficient of the variable X to variable Y rxy = 0, 668 is highly significant (where t-count equal 4, 745) t-table = 1,697 to = 0, 05). Thus there is a significant and positive relation ship between the use of facility to the learning out comes of student studying fine arts at SMPN 1 Batang Anai.